PEMETAAN LOKASI RAWAN KECELAKAAN KERETA API DI KOTA PADANG - Reni Puspa Handayani; Triyatno Triyatno (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
This research of aims are : 1) determine the location of accident vulnerability (black site) and the of train accident in Padang City. 2) know the characteristics of the location vulnerability to accident (black site) of train. 3) know the effort that have been and will be implemented in overcoming the train accident in Padang City. This type of research is descriptive with a quantitative appoarch. In analyzing the location of the train accident vulnerability, researchers use the equivalent accident number method and the upper control limit method. The results of this research are the location of accident vulnerability (black site) railway identified at the crossing on the intersection of Anak Air Kelurahan Lubuk Buaya, Intersection of High School 7 Bungo Tanjung Street, and Kilometer 18, between Tabing station and Duku station. In general the characteristic location of the train accident vulnerability to the lack of rail crossing doors, the lack of railway traffic signs and the human lifestyle. Effort hass been implemented overcoming the vulnerable of train accident is to close the door of the wild crossing the train and is that very crossing of the railway will be closed and then given the diversion street collector in the form of a flay over.